Faktor-faktor yang Mempengaruhi Konversi Lahan serta Dampaknya Terhadap Kesejahteraan Petani: Kasus di Subak Jadi, Kecamatan Kediri, Kabupaten Tabanan - I Made Mahadi Dwipradnyana; Wayan Windia; I Made Sudarma (JURNAL MANAJEMEN AGRIBISNIS, 2015)
Land conversion is a process of change in land use of a particular form of usage become another example to non-agricultural use. Conversion of agricultural land to non-agricultural agricultural development is a central issue that can have a significant impact on food production, economic and social aspects of environmental aspects. Conversion phenomenon is basically the result of the competition between agricultural land use to non-agricultural sector arising from the three economic and social phenomena are limited natural resources, population growth and economic growth. Viewing the phenomenon of this research was conducted in order to find the factors that affect the conversion of land either as a motivating factor as well as towing. Furthermore, of these factors can be analyzed to see its effect on the welfare of farmers converting land in Subak Jadi District of Kediri, Tabanan. The method used in this study is a quantitative method. Sources of data used in this study using primary data source is by distributing questionnaires directly to farmers and secondary data sources to find data from BPS and other relevant sources. Sampling of the population is performed using Slovin formula. Data analysis method used is the method of factor analysis, multiple linear regression and paired sample t test with a standard error of 5% (? = 0.05). Research results obtained are all variables simultaneously and significantly affect the conversion. Partial conversion of the driving factors of land there are just external push factors have a significant effect. The variable is the soil quality, housing needs, and the opportunity to buy land elsewhere. Suggestion for reducing lan conversion is the government should reinforce the regulations in the field of licensing, especially to build in wetlands. Government should also tighten the rules of buying and selling land, especially agricultural land should be sold but kept for agricultural land.